Specifics of the students’ critical thinking formation within active learning space - Solovyeva, Nataliya; Tapalova, Olga; Smirnov, Sergei (Frontiers in Education, 2023)
Critical thinking skills are important for personal development and self-realization in professional activity. Thus, this research was aimed at obtaining data about the formation of students’ critical thinking and the professional competencies of the future specialist within hybrid learning. The developed elective course for psychologists and linguists was introduced into the educational system of a higher educational institution. To measure the level of forced critical thinking, the authors used the California Critical Thinking Disposition Inventory (CCTDI), which is specifically designed for undergraduate and graduate students or comparable groups. The findings describe the specifics of the students’ critical thinking formation within hybrid learning. The statistical data analysis showed positive dynamics and a significant increase in the experimental group. The practical testing and experimental validity of the developed course effectiveness gives prospects for further studies of this phenomenon and the practical implementation of innovative technologies aimed at the students’ critical thinking formation within a blended learning model in higher education institutions. The developed optional course within the blended learning model allows creating and practically implementing new educational programs for university students. The research findings also foresee the need for further study of training competent pedagogical staff for the implementation of blended learning.